Q: If a plus b equals c then c - b equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

the answer is a

A=0 b=0 c=0

b + b + b + c + c + c + c = 3b + 4c

2a. (a, b and c are all equal.)

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

Related questions

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)

the answer is a

Because there is no way to define the divisors, the equations cannot be evaluated.

a=24 b=16 c=18

A=0 b=0 c=0

b + b + b + c + c + c + c = 3b + 4c

a = 20 b = 60 c = 100

2a. (a, b and c are all equal.)

A+c= 2a+b

7.5

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

Ax + B = Bx + C Ax - Bx = (C - B) x (A - B) = (C - B) x = (C - B) / (A - B)